M dwarf stars in the light of (future) exoplanet searches. Issue 1 (6th February 2013) - Rojas‐Ayala, B.; Hilton, E.J.; Mann, A.W.; Lépine, S.; Gaidos, E.; Bonfils, X.; Helling, Ch.; Henry, T.J.; Rogers, L. A.; von Braun, K.; Youdin, A.
Abstract We present a brief overview of a splinter session on M dwarf stars as planet hosts that was organized as part of the Cool Stars 17 conference. The session was devoted to reviewing our current knowledge of M dwarf stars and exoplanets in order to prepare for current and future exoplanet searches focusing in low mass stars. We review the observational and theoretical challenges to characterize M dwarf stars and the importance of accurate fundamental parameters for the proper characterization of their exoplanets and our understanding on planet formation. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)